Phosphorus price spikes: A wake-up call for phosphorus resilience - Brownlie, Will J.; Sutton, Mark A.; Cordell, Dana; Reay, Dave S.; Heal, Kate V.; Withers, Paul J. A.; Vanderbeck, Isabelle; Spears, Bryan M. (Frontiers in Sustainable Food Systems, 2023)
• Food systems depend on reliable supplies of phosphorus. • Since 2020, a pandemic, geopolitical disputes, trade wars and escalating fuel prices have driven a >400% increase in phosphorus commodity prices. • The Russia-Ukraine conflict has disrupted phosphate trade further. • Concurrently, phosphorus losses to freshwaters are a significant threat to water quality globally. • However, nations are unaware of their ‘phosphorus vulnerability’ and phosphorus is absent in policies. • We discuss the current price spike; drivers, policy responses and their consequences. • We highlight the need for an integrated assessment of phosphorus vulnerability that considers environmental, socio-economic and climate change risks. • Reducing phosphorus waste, increasing recycling and wider system transformation can reduce national reliance on imported phosphorus, whilst enhancing food and water security.